PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN (STUDI PADA KARYAWAN ALPHA HOTEL PEKANBARU) - Silvia Anggreini; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of work environment  and organizational commitment of employee turnover intention Alpha Hotel pekanbaru. Loyalty is one of the factors that makes company’s goals run in accordance with applicable rules and norms. To reduce the turnover of intent on to subject of what affects the turn of intent. For that organization’s commitment factor has a role to direct the individual. In addition, work environment also have a bearing on one’s behavior. The population of this study is employee Alpha hotel pekanbaru with 66 people calculated using samples census. Data retrieval methods in the research of primary and secondary with using questionnaires, interviews and documents that are on company. The analysis of data is use the application of SPSS ver 25 for windows.            The study suggests that the result of the t indicates that the work environment has a negative impact on the Alpha Hotel employee turnover. The result t suggest that the organizational commitment has a negative impact on the position of Alpha Hotel Pekanbaru employee turnover. The results indicate that the work environment and organizational commitment simultaneously have a negative impact turnover intenton.  Keywords: work environment, organizational commitment, turnover intention